Landscape divergence associated with international borders and economic asymmetries - Grau, Hector Ricardo (2022)
Land cover divergences across international borders reflect how country-level policies influence ecological footprints on the landscape. We identified 30 abrupt transboundary divergences across the globe, with major land cover differences despite similar ecological conditions. Divergences were significantly associated with differences in Gross Domestic Product (GDP) between countries, not with demographic differences. In mountains, unsuitable for mechanized agriculture, wealthier countries have higher forest cover and urbanization, suggesting advanced ‘forest transitions’. Lowlands with rainfed agricultural potential showed more agriculture development on the wealthier side of the border, except when the country´s economy was not based on agriculture. In drylands, wealthier countries showed much more irrigation-based agriculture. Despite globalization, transboundary divergences are unlikely to disappear and may even intensify, thus meriting increased research attention as a distinctive feature of Anthropocene ecology.